2014
DOI: 10.1177/0306624x14553227
|View full text |Cite
|
Sign up to set email alerts
|

“They Treat Us Like Human Beings”—Experiencing a Therapeutic Sex Offenders Prison

Abstract: Research evidence demonstrates that sex offender treatment programmes (SOTPs) can reduce the number of sex offenders who are reconvicted. However, there has been much less empirical research exploring the experiences and perspectives of the prison environment within which treatment takes place. This is important, particularly for sexual offenders, as they often face multiple stigmas in prison. This study used a mixed-methods approach to explore the experiences of prisoners and staff at a therapeutically orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 51 publications
4
74
0
4
Order By: Relevance
“…As shown by Blagden et al (2014), professionals who work therapeutically with sexual offenders generally hold incremental ITs. Future research should examine these concepts further in order to establish whether professionals' ITs have an effect on the efficacy of sexual offender training.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Blagden et al (2014), professionals who work therapeutically with sexual offenders generally hold incremental ITs. Future research should examine these concepts further in order to establish whether professionals' ITs have an effect on the efficacy of sexual offender training.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition, Skitka et al found an interaction between IT classification and political ideology, with conservatives being more likely to hold entity ITs and liberals endorsing more incremental views. Blagden, Winder, and Hames (2014) recently reported a moderate positive correlation between incremental ITs about sexual offending and attitudes towards sexual offenders. That is, as attitudes towards sexual offenders became more positive, so too did the belief in an offender's ability to change.…”
mentioning
confidence: 98%
“…This implication is perhaps most critical within clinical contexts, where risk assessments can be the difference between release and continued incarceration. Indeed, Blagden et al (2016) highlighted that professionals' IT orientations (about offending behaviour generally) were correlated with their attitudes towards sexual offenders. In a separate study, Hogue (2015) reported a significant correlation between attitudes towards sexual offenders and perceptions of re-offending risk among a sample of licenced forensic psychologists.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two studies have specifically applied this framework to attitudes towards sexual offenders. First, Blagden, Winder, and Hames (2016) found that forensic professionals with a more incrementally based IT about offending behaviour (in a general sense) expressed more positive attitudes towards sexual offenders than those with an IT that was entity-based. In turn, these attitudes were associated with their approach to treatment and engagement with inmates at a therapeutic prison for people convicted of sexual offences.…”
Section: Aq2mentioning
confidence: 99%
“…A total MRNI-A-r score is obtained through the averaging of scores on all 29 items. The Implicit Theory of Offending Behaviour (Blagden et al, 2014) is a reimaging of the domainspecific implicit theories of intelligence and personality, and Gerber and O 'Connell's (2012) implicit theory of crime and criminality (self and other). The 'implicit theory of offending behaviour (self)'…”
Section: Methodsmentioning
confidence: 99%